Spatial analysis of urban expansion and its effects on land surface temperature using geospatial techniques in Addis Ababa and Shaggar Cities, Ethiopia - Mitiku Badasa Moisa; Dugassa Negash; Zenebe Reta Roba; Gemechu Debesa Wedajo; Kiros Tsegay Deribew; Fedhasa Benti; Dessalegn Obsi Gemeda (All Earth)
Ethiopia has been experiencing an extremely high rate of urban expansion, which increases urban surface temperature. This study aimed to analyse the impact of urban expansion on land surface temperature (LST) using geospatial techniques in the rapidly expanding cities of Addis Ababa and Shaggar city. Landsat TM of 1994, Landsat ETM+ of 20,09, and Landsat OLI/TIRS of 2024 were used for Land use land cover (LULC) classification and LST calculation. In addition, the Normalised Difference Vegetation Index (NDVI) and Normalised Built-up Index (NDBI) were calculated using multispectral bands at various levels. The result revealed that agriculture land was converted to built-up area with 450.4 m2 (22.1%) from 1994 to 2024. As a result, the maximum value of NDVI was decreased with 0.12, whereas NDBI was increased by 0.25 from 1994 to 2024. The LST was increased by the mean of 4.4°C due to an increase in impervious surfaces. Therefore, the finding recommended that, strengthening and scaling up the conservation of green area by initiative Green Legacy Program to mitigate the increasing trend of LST. Discouraging horizontal expansion and encouraging vertical city growth by the urban planners and policymaker can reduce LST.